1999
DOI: 10.1046/j.1365-2540.1999.00620.x
|View full text |Cite
|
Sign up to set email alerts
|

Crosses between sexual and apomictic dandelions (Taraxacum). II. The breakdown of apomixis

Abstract: Some dandelions are diplosporous gametophytic apomicts. In order to study the inheritance and breakdown of apomixis, crosses were made between diploid sexuals and triploid apomicts. To investigate their breeding system, four nonapomictic diploid and 10 nonapomictic triploid hybrids were pollinated with diploids and the progenies were analysed. Seed fertility was signi®cantly reduced in two diploid hybrids. Nine triploid hybrids were fertile and could be classi®ed into three types, with respect to the compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(50 citation statements)
references
References 20 publications
0
47
3
Order By: Relevance
“…The presence of varied apomictic mechanisms and the phylogenetic positioning of apomictic species throughout many angiosperm families together imply that apomixis has evolved independently multiple times (Carman 1997;Van Dijk and Vijverberg 2005). Genetic analyses using apomicts as pollen donors in crosses with sexual individuals as maternal parents have shown apomixis to be inherited as a dominant trait.…”
Section: Genetics and Inheritance Of Apomixismentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of varied apomictic mechanisms and the phylogenetic positioning of apomictic species throughout many angiosperm families together imply that apomixis has evolved independently multiple times (Carman 1997;Van Dijk and Vijverberg 2005). Genetic analyses using apomicts as pollen donors in crosses with sexual individuals as maternal parents have shown apomixis to be inherited as a dominant trait.…”
Section: Genetics and Inheritance Of Apomixismentioning
confidence: 99%
“…Studies involving genetic analyses searching for rare recombinants in suppressed regions and gamma deletion mutagenesis have revealed that in some species, the developmental components of apomixis (meiotic avoidance, parthenogenesis, and fertilization-independent endosperm development) are controlled by independent loci. For instance, in Taraxacum and Erigeron species, two independent loci have been identified that control diplospory and parthenogenesis (Van Dijk et al 1999;Noyes and Rieseberg 2000). Similarly, apospory and parthenogenesis are controlled by two independent loci in Hypericum, Poa, Hieracium, and Cenchrus species (Albertini et al 2001;Catanach et al 2006;Schallau et al 2010;Conner et al 2013).…”
Section: Genetics and Inheritance Of Apomixismentioning
confidence: 99%
“…Variation in the reproductive behavior within a single individual is common in both natural and artificial apomicts (Koltunow et al, 2000, Leblanc, 1995, Nogler, 1984, Noyes, 2005, Richards, 1996, Van Dijk et al, 1999. In order to assess the nature and the extent of variation in reproductive behavior in 38C, an apomictic clone, we collected flow cytometrical, cytogenetical and molecular data within progenies obtained after pollination using 2x maize progenitors.…”
Section: Reproduction In 38-chromosome Apomictic Clones Can Occur Thrmentioning
confidence: 99%
“…In aposporous Poa pratensis (Poaceae), for example, apomeiotic individuals (identified cytologi-cally) constituted 5% of F1s (Albertini et al, 2001). In diplosporous Taraxacum officinale (Asteraceae), six of 19 F1s (32%) were identified as apomeiotic, producing at least some 2n þ n and no 2n þ 0 offspring progeny when test-crossed (van Dijk et al, 1999). In Erigeron (Asteraceae), diplosporous plants constituted 23% (30/130) of an F1 mapping population generated by crossing apomictic E. annuus with sexual E. strigosus.…”
Section: Introductionmentioning
confidence: 99%